Factors affecting domestic tourists’ repeat purchase intention towards accommodation in Malaysia - SPR, Charles Ramendran; Yong, Hui Nee Au; Kalhoro, Maryam; Dahari, Kamarulzaman Bin Mohd; Shaikh, Farhan Bashir (Frontiers in Psychology, 2023)
The hospitality and tourist industries depend on homestays and accommodations. Different factors, i.e., promotion strategies, service quality, cleanliness, and perceived health risks, influence tourists' repeat purchase intention for accommodation. This study highlights different variables influencing domestic tourists' accommodation repurchase decisions in Malaysia. Around 304 respondents from this quantitative survey are tourists who have already experienced choosing their accommodations during travel. Statistical Packages of Social science software (SPSS-23.0) were used to examine the data through multiple regression and descriptive approaches. The finding suggests that promotion, and services, can positively affect visitors' purchasing decisions. However, there is a negative but statistically significant link between perceived health risk and repurchase decisions. Furthermore, the result revealed that the predictors of purchase decisions significantly influence selection. This study observed the undervalued quality of services and facilities provided by the hotel industry. The results identified that sustainable practices could enhance the impressive recovery of the tourism industry during and after the pandemic. Furthermore, cleanliness and cost are vital to be considered a primary quality service factor, reducing the perceived health risk, even if there is a pandemic. The study suggested that lodging providers could upgrade on-site facilities and acquire better promotion strategies. The study's conclusions can increase satisfaction to avoid health risks in any circumstance and promote tourism.